Venture capital investment:survey on problems and prospects faced by the entrepreneur - ROBERT, MR.P.WILLIAM; R, MS.JENAPRIYA (The journal of contemporary issues in business and government, 2020)
The research project titled A study on venture capital investment and survey on problems and prospects faced by the entrepreneur. This paper studies problems and prospects of the entrepreneur on venture capital investment and importance of venture capital investment. Descriptive research is applied using a convenience method of sampling with 60 respondents. The tools used for the study are mean analysis, frequency analysis, Independent t test, ANOVA and factor analysis. It is found that individuals seeking venture capital might need to adjust their approach to different capitalists, recognising the diversity involved. Niche’s of venture capital exist due to structure and rules of capital markets.